Mechanistic insights into p53‐regulated cytotoxicity of combined entinostat and irinotecan against colorectal cancer cells. Issue 12 (29th July 2021) - Marx, Christian; Sonnemann, Jürgen; Beyer, Mandy; Maddocks, Oliver D. K.; Lilla, Sergio; Hauzenberger, Irene; Piée‐Staffa, Andrea; Siniuk, Kanstantsin; Nunna, Suneetha; Marx‐Blümel, Lisa; Westermann, Martin; Wagner, Tobias; et al.
Abstract : Late‐stage colorectal cancer (CRC) is still a clinically challenging problem. The activity of the tumor suppressor p53 is regulated via post‐translational modifications (PTMs). While the relevance of p53 C‐terminal acetylation for transcriptional regulation is well defined, it is unknown whether this PTM controls mitochondrially mediated apoptosis directly. We used wild‐type p53 or p53‐negative human CRC cells, cells with acetylation‐defective p53, transformation assays, CRC organoids, and xenograft mouse models to assess how p53 acetylation determines cellular stress responses. The topoisomerase‐1 inhibitor irinotecan induces acetylation of several lysine residues within p53. Inhibition of histone deacetylases (HDACs) with the class I HDAC inhibitor entinostat synergistically triggers mitochondrial damage and apoptosis in irinotecan‐treated p53‐positive CRC cells. This specifically relies on the C‐terminal acetylation of p53 by CREB‐binding protein/p300 and the presence of C‐terminally acetylated p53 in complex with the proapoptotic BCL2 antagonist/killer protein. This control of C‐terminal acetylation by HDACs can mechanistically explain why combinations of irinotecan and entinostat represent clinically tractable agents for the therapy of p53‐proficient CRC. Abstract : Irinotecan induces post‐translational modification of p53, DNA repair by homologous recombination (HR), and p53 target gene expression. Entinostat and irinotecan combinations increase the C‐terminal acetylation and reduce the N‐terminal phosphorylation of p53, and impair p53 target gene transcription and HR. This drug combination additionally alters the expression and activity of BCL2 proteins and promotes the complex formation of acetylated p53 and BAK. These mechanisms subsequently trigger mitochondrial membrane permeabilization that leads to intrinsic apoptosis.